The balance of payments of Nigeria in 1936 - Bower, Penelope A. (Oxford : B. Blackwell, 1949)
This volume comprise the Statistical analyses of balance of payments in Nigeria in 1936 , pointing out the effect of all economic relations between Nigeria and the outside world.
Bibliography: p. 77-81.
sju 24/01/2019
Loans
Keywords: Balance of trade; International trade; Economic conditions; Nigeria